PROF. DR VITOMIR POPOVIĆ, MR BORIS TOPIĆ, SLAĐANA MARIĆ: “NULLUM CRIMEN, NULLA POENA SINE LEGE U MEĐUNARODNOM PRAVU I PRAVU BIH IN THE CONTEXT OF PROSECUTING A WAR CRIMES AND CRIMES AGAINST HUMANITY”, BANJA LUKA, 2008. - Knežević, Saša (Law - Theory and Practice, 2010)
-